Do religiosity and knowledge affect the attitude and intention to use halal cosmetic products? evidence from Indonesia - Monicha Divianjella; Istyakara Muslichah; Zafirah Hanoum Ahmad Ariff (Asian Journal of Islamic Management (AJIM), 2020)
Purpose: This study aims to examine the roles of religiosity and knowledge on attitude formation towards Halal cosmetic products. The attitude toward Halal cosmetic products will then be further investigated to determine whether it affects the intention to purchase Halal cosmetics in the domestic cosmetic industry in Indonesia.Methodology: This study utilized the purposive sampling method to collect the data. A total of 150 Indonesian Muslim consumers who have previously used Halal cosmetic products participated in this survey. Structural equation modeling was used to test the hypotheses in this study.Findings: The results showed that both religiosity and product knowledge significantly impact attitude towards using Halal cosmetics products. Interestingly, the findings revealed that product knowledge has a higher impact on attitude compared to religiosity. More importantly, attitude towards Halal cosmetics also showed a positive effect on the intention to use Halal cosmetics products.Originality: Previous research in the Malaysian context conducted by Abd Rahman et al. (2015) and Suki and Suki (2018) formed as the basis of this study. Although the same theme and hypotheses were incorporated, however, the current study was examined in a different market setting and on a different set of respondents (i.e., Indonesian Halal market).